Penelusuran Profil Kadar Gula Darah Sewaktu pada Pria dan Wanita Usia Produktif di SMA Kalam Kudus II, Duri Kosambi, Jakarta - Sari, Triyana; Satyo, Yovian Timothy; Mashadi, Fladys Jashinta; Destra, Edwin (LPPM Universitas 17 Agustus 1945 Semarang, 2024)
Temporary blood sugar is the level of glucose in the blood that measured without considering the time of the last meal, and often used to detect diabetes mellitus or impaired glucose tolerance. This community service activity aims to describe the distribution of blood sugar levels in 68 men and women of productive age at Kalam Kudus II High School, Jakarta. This community service activity is carried out using the Plan-Do-Check-Action method. The results showed that the majority of respondents had normal fasting blood sugar levels (97.1%), with an average of 113.26 mg/dL and a median of 104 mg/dL. Lifestyle factors, nutrition, genetics, and chronic medical conditions can affect blood sugar levels at any time. Regular monitoring of blood sugar levels is essential for early detection and management of diabetes mellitus, which can prevent serious complications such as cardiovascular disease and nephropathy. Prevention strategies include a healthy diet, physical activity, patient education, and appropriate medical interventions. Comprehensive public health programs are needed to increase awareness and management of diabetes, as well as improve the quality of life of individuals affected by this disease.